Thismia kobensis (Burmanniaceae), a new and presumably extinct species from Hyogo Prefecture, Japan - Suetsugu, Kenji; Nakanishi, Osamu; Kobayashi, Tomiki; Kurosaki, Nobuhira (Phytotaxa, 2018)
Thismia Griffith (1844: 221), Thismiaceae J. Agardh or Burmanniaceae sensu APG VI (2016), is one of the most species-rich mycoheterotrophic genera, consisting of ca. 80 species (Jonker 1948, Merckx et al. 2013). Considering that most of these species were collected only once (Jonker 1948) and that many new species have recently been discovered in various Asian countries (e.g. Suetsugu et al. 2017, 2018), many more undescribed species are likely in these regions.